2012
DOI: 10.5402/2012/680598
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Indoor Air Quality in Archives and Biodeterioration of the Documentary Heritage

Abstract: Documentary heritage is permanently subject to suffering from physical, chemical, and/or biological alterations. Biological deterioration by microorganisms (bacteria and fungi) causes undesirable changes on material properties. Microorganisms affect different organic, natural or synthetic substrates (cellulose, polycarbonates), metals, and compounds of optical and magnetic devices (CD, VHS). Paper made by vegetal fibers, functional additives (glue, optical polishers, consolidating agents), and inks with organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 35 publications
2
63
0
11
Order By: Relevance
“…They however differed in their mode of result presentation. Of the 5 studies, only 2 represented the results of their study as CFU/m 3 (Udochukwu et al, 2015;Emuren and Ordinioha, 2016).These studies did not however describe how these values were obtained, and reported values ranging from 5.33 -227.33 CFU/m 3 . Two other studies (Wemedo et al, 2012;Agbagwa and Onyeamachi, 2014) presented their results as CFU/30min and simply as "no of colonies".…”
Section: Literature Review/summary Of Literaturementioning
confidence: 95%
See 2 more Smart Citations
“…They however differed in their mode of result presentation. Of the 5 studies, only 2 represented the results of their study as CFU/m 3 (Udochukwu et al, 2015;Emuren and Ordinioha, 2016).These studies did not however describe how these values were obtained, and reported values ranging from 5.33 -227.33 CFU/m 3 . Two other studies (Wemedo et al, 2012;Agbagwa and Onyeamachi, 2014) presented their results as CFU/30min and simply as "no of colonies".…”
Section: Literature Review/summary Of Literaturementioning
confidence: 95%
“…Total bacterial count was determined using nutrient agar (NA). Following this, CFU/m 3 determined using the Omeliansky equation (Borrego et al, 2012) N = 5a × 10 4 (bt) -1 .…”
Section: Determination Of Bacterial Load 'Pre-black Soot'mentioning
confidence: 99%
See 1 more Smart Citation
“…EOs have seldom been tested in vitro against fungi isolated from cultural heritage objects. Examples include isolates from the documentary heritage (Borrego et al 2012a), royal tomb paintings (Sakr et al 2012), stone and wooden artifacts (Stupar et al 2014). Reports regarding the implementation of natural products in the fi eld of conservation of cultural heritage are scarce.…”
Section: Morpho-physiological Changesmentioning
confidence: 99%
“…(Garg et al 1995, Florian 2002. They are also involved in the degradation of a broad range of organic substrata (Goldman and Osmani 2007) due to their proteolytic, cellulolytic and amylolytic activity (Borrego et al 2010, 2012a, Eida et al 2011. A vast number of microfungi, including Aspergillus species, are able to produce different organic and inorganic acids during their metabolic activities on monument surfaces (Farooq et al 2015).…”
Section: Introductionmentioning
confidence: 99%